Retinol binding protein‐4 predicts incident diabetes in Asian Indian men with prediabetes. (23rd March 2015) - Ram, Jagannathan; Snehalatha, Chamukuttan; Selvam, Sundaram; Nanditha, Arun; Shetty, Ananth Samith; Godsland, Ian F.; Johnston, Desmond G.; Ramachandran, Ambady
Abstract The association of retinol binding protein‐4 (RBP4) with incident type 2 diabetes (T2DM) in Asian Indian middle‐aged men with impaired glucose tolerance (IGT) was studied. This was an ancillary analysis of a subsample from a cohort of participants with IGT in a 2 year prospective diabetes prevention program in India. For this analysis, 71 incident T2DM and 76 non‐diabetic cases (non‐progressors) based on the final glycemic outcome were selected. Baseline serum RBP4 was measured using competitive enzyme immunoassay. Correlations of RBP4 with relevant anthropometric and biochemical variables and also its association with diabetes were assessed using appropriate statistical analyses. Participants who developed T2DM had higher levels of serum RBP4 (21.3 [IQR: 17.7–24.9] µg/mL) compared with non‐progressors (17.3 [IQR: 13.1–21.0] µg/mL; P = 0.001). Levels of RBP4 were lower than in Caucasians. Stepwise linear regression analysis showed that body mass index (BMI), systolic blood pressure, triglycerides, and HbA1c had independent associations with RBP4 levels. Multiple logistic regression analyses showed that RBP4 was independently associated with incident diabetes (odds ratio [OR] [95%confidence interval (CI)]: 1.69 [1.18–2.41]; P = 0.004). Adjustment for study group, age, BMI, waist circumference, 2 H plasma glucose, triglycerides, gamma glutamyl transferase, and insulin resistance weakened the significance of its association (OR [95%CI]: 1.65 [1.03–2.66]; P = 0.038).The results of this preliminary analyses showed that baseline serum RBP4 levels were independently associated with incident diabetes in Asian Indian men with IGT. It may be used as an additional predictor of future diabetes. © 2015 BioFactors, 41(3):160–165, 2015